Engineering lecturers’ and students’ perceptions about teaching and learning practices in a South African University of Technology - Selepe, Mamoraka Caroline (Curtin University, 2011)
This thesis investigated engineering lecturers’ and students’ perceptions about teaching and learning practices in the Faculty of Engineering at a South African University of Technology. The Faculty of Engineering had experienced low student success rates in many of its programmes and courses over a long time. This study was premised upon the concern that the teaching knowledge competencies of the engineering lecturers might be inadequate to facilitate meaningful learning and to motivate their students to learn better and achieve excellent success rates. The overarching construct of investigation was the lecturers’ teaching knowledge. The teaching and learning theories of constructivism and pedagogical content knowledge were used as the main frameworks which guided the study. The teaching knowledge domains investigated in this study were instructional repertoire, representational repertoire, subject matter knowledge, and knowledge of student understanding. Sources of the lecturers’ teaching knowledge professional development were also investigated.The study was approached from two perspectives – the students’ and lecturers’ views on teaching and learning. Three research questions guided this study. 1. What are students’ perceptions of their lecturers’ teaching knowledge in their engineering classrooms? 2. What are the lecturers’ perceptions of their own teaching knowledge in engineering classrooms? 3. What are the lecturers’ perceptions of their own professional development?A mixed methods design incorporated qualitative and quantitative approaches and techniques to collect and analyse data. Students completed the Students’ Perceptions of Teacher Knowledge (SPOTK) questionnaire. Lecturers completed the Teachers’ Beliefs about Teaching and Learning in Engineering Questionnaire (TBTLE). Data from 450 completed students questionnaires and 24 completed lecturers questionnaires and interviews with nine lecturers were used to provide answers to the three research questions. The SPOTK and TBTLE questionnaires were found to be both valid and reliable instruments in this higher education context.The main findings from the study: Students and lecturers perceived teaching knowledge in their classrooms both positively and negatively. Teacher–centred teaching approaches and strategies were still predominantly used in many of the classrooms. Many lecturers had limited knowledge about teaching. Both students and lecturers raised concerns about the ineffectiveness of teaching methodologies and assessment practices to facilitate meaningful learning. Lecturers perceived their teaching approaches and students’ attitude towards learning as possible causes of low success rates. The findings confirmed that teaching and learning approaches used by lecturers were not consistent with the teaching and learning theories supported by constructivism and pedagogical content knowledge principles. Lecturers’ participation in teaching professional development was based on personal choices. The most predominant sources of professional development were associated with advancement of disciplinary knowledge as opposed to collegiality and attendance of teaching and learning development courses. In addition, both lecturers and students raised dissatisfaction with the some aspects of the engineering curriculum structure and psychosocial factors of an affective nature as possible causes of teaching and learning difficulties.This study has successfully identified limitations in lecturers’ knowledge of teaching. The information has implications for the conceptualisation of teaching knowledge in professional development for engineering lecturers. The findings have the potential to influence curriculum reform in engineering in South Africa. Therefore curriculum design, planning and implementation by decision makers may benefit from the use of these findings.In conclusion, the study has revealed that the SPOTK and TBTLE questionnaires, used for the first time in a higher education environment, were successful in eliciting students’ and lecturers’ perceptions about teaching and learning practices in engineering classrooms. This finding adds to the body of knowledge in the use of these tools in teaching knowledge studies.